Systems Integration and Project Management - Abu Bakar, Zaitun; Baharum, Noriati; Yaacob, Mashkuri (Malaysian Journal of Computer Science, 2001)
This paper is based on a survey carried out in the Malaysian public sector and a prototype system developed to assist in project management. The paper starts with a definition of Systems Integration and this is followed by a description of its current status in the Malaysian public sector. Focus is then drawn to the Project Monitoring System (SETIA), which is an information system used to monitor the progress of all government-sponsored projects implemented by ministries and agencies. This is followed by a discussion on how systems integration techniques can be used to eliminate some of the obstacles faced. A prototype system embodying the proposed solution was then developed and tested. Based on the feedback obtained from the use of the prototype system, a conclusion is drawn on the appropriateness of the systems integration technique in the area of project management.